On the boundary estimates for the distortions of mappings in domains with Poincaré inequality - Sevost’yanov, E.; Baronova, M.; Dovhopiatyi, O.; Ilkevych, N. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We study the mappings that distort the modulus of the families of paths according to the Poletsky-inequality type. At the boundary points of a domain, we obtain estimates for the distortion of  distances to these mappings provided that their characteristic either has a finite mean oscillation at every point or satisfies the Lehto-type integral conditions, while the mapped domain is Ahlfors regular and satisfies the Poincar\'e inequality. The  cases of homeomorphisms and mappings with branching  are analyzed, as well as  the domains with good boundaries and  domains with prime ends.